Forests for the People The Story of America$1 (Bs Eastern National Forests /s - Johnson, Christopher; Govatski, David; SpringerLink (Online service) (Washington, DC : Island Press/Center for Resource Economics : Imprint: Island Press, 2013)
Forests for the People tells one of the most extraordinary stories of environmental protection in our nation$1 (Bs history: how a diverse coalition of citizens, organizations, and business and political leaders worked to create a system of national forests in the Eastern United States. It offers an insightful and wide-ranging look at the actions leading to the passage of the Weeks Act in 1911$1 (Blandmark legislation that established a system of well-managed forests in the East, the South, and the Great Lakes region$1 (Balong with case studies that consider some of the key challenges facing eastern forests today. The book begins by looking at destructive practices widely used by the timber industry in the late 1800s and early 1900s, including extensive clearcutting followed by forest fire that devastated entire landscapes. The authors explain how this led to the birth of a new conservation movement that began simultaneously in the Southern Appalachians and New England, and describe the subsequent protection of forests in New England (New Hampshire and the White Mountains); the Great Lakes region (Michigan, Wisconsin, and Minnesota), and the Southern Appalachians. Following this historical background, the authors offer eight case studies that examine critical issues facing the eastern national forests today, including timber harvesting, the use of fire, wilderness protection, endangered wildlife, oil shale drilling, invasive species, and development surrounding national park borders. Forests for the People is the only book to fully describe the history of the Weeks Act and the creation of the eastern national forests and to use case studies to illustrate current management issues facing these treasured landscapes. It is an important new work for anyone interested in the past or future of forests and forestry in the United States.s
Acknowledgment -- Introduction -- Part I. How the Eastern National Forests Were Saved. 1. The Disappearing Forests of the White Mountains -- 2. Trees to Build the Lake States -- 3. A Forest Crisis in the Southern Appalachians -- 4. Building a Forest Conservation Movement -- 5. Legislation at Last: The Weeks Act -- 6. Creating the Eastern National Forests -- Part II. Issues Facing the Eastern National Forests Today. 7. Holly Springs National Forest: A Study in Forest Management Reform -- 8. Florida$1 (Bs National Forests: A Revolution in Prescribed Burning -- 9. Monongahela National Forest: Wilderness at Heart -- 10. Boundary Waters Canoe Area Wilderness: Preservation versus Multiple Use -- 11. Ottawa and Hiawatha National Forests: The Return of the Wolf -- 12. Allegheny National Forest: The Challenges of Shale Oil Drilling -- 13. Michigan$1 (Bs National Forests: The Invasion of the Emerald Ash Borer -- 14. National Forests of Vermont and North Carolina: Loving the Forests to Death -- Conclusion -- Notes -- Selected Bibliography -- About the Authors -- Index.s
Keywords: Environmental sciences; Ecology; Endangered ecosystems; Conservation biology; Forests and forestry; Environment; Environment, general; Ecology; Forestry; Conservation Biology/Ecology.; Ecosystems